A Concise Synthesis of 3-Arylated Di- and Tetrahydro-2H-2-benzazepin-1-ones; A New Synthetic Approach to the Homoprotoberberine Framework - Lebrun, Stéphane; Couture, Axel; Deniau, Eric; Grandclaudon, Pierre (Synthesis, 2012)
A variety of 3-arylated di- and tetrahydro-2H-2-benzazepin-1-ones were efficiently assembled through a sequence involving a Suzuki–Miyaura cross-coupling reaction with enol phosphates derived from the corresponding benzazepine-1,3-diones. This technique has been further exploited for the construction of the homoprotoberberine skeleton, which was readily accessed by intramolecular carbocationic annulation reaction applied to a suitably substituted precursor.
Keywords: fused-ring systems; metathesis; cross-coupling; enols; ring closure